Identification of dna barcode sequence of hybrid eucalyptus UP99 (E. urophylla x E. pellita) and UP95 (E. urophylla x E. pellita) to identify plant varieties - Thi Mai Huong, Bui; Van Huan, Ha; Tho Son, Le (Journal of Forestry Science and Technology, 2023)
The hybrid Eucalyptus UP99 (E. urophylla x E. pellita) and UP95 (E. urophylla x E. pellita) were recognized as a high economic value species according to Decision 65/QĐ-BNN-LN on January 11th in 2013. However, it is very difficult to the famer in identifying these species by morphological observation. Therefore, this study aimed to develop a method using DNA barcode fragments to identify the hybrid Eucalyptus UP99 and UP95. The total genomic DNA was extracted from leaf samples of UP99 and UP95 and was used to amplify the DNA barcodes (matK, rbcL, trnH-psbA, ITS and ITS2) by PCR. The results showed that the bands of PCR production have the expected size, which is 643 bp, 743 bp, 626 bp, 563 bp, and 250 bp for matK, rbcL, trnH-psbA, ITS, and ITS2 fragment, respectively. After that, these sequences were aligned with the sequence of those genes of other Eucalyptus species in NCBI. The results showed that UP99 with matK, rbcL and trnH-psbA gene fragments are 100% similar to UP95, ITS gene fragment is 99.81% similar to UP95, ITS2 gene fragment is 98.86% similar to UP95. These results suggest that it is best for using ITS2 and ITS molecular marker as a DNA barcode to identify Hybrid Eucalyptus UP99 (E. urophylla x E. pellita) and UP95 (E. urophylla x E. pellita) in Vietnam. These results are an important basis for the identification hybrid Eucalyptus UP99 (E. urophylla x E. pellita) and UP95 (E. urophylla x E. pellita).